Medicinal plants for treating musculoskeletal disorders among karen in thailand - Rapeeporn Kantasrila (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Millions of people suffer from Musculoskeletal System Disorders (MSDs), including Karen people who work hard in the fields for their subsistence and have done so for generations. This has forced the Karen to use many medicinal plants to treat MSDs. We gathered data from 15 original references covering 27 Karen communities and we document 461 reports of the use of 175 species for treating MSDs among the Karen people in Thailand. The data were analyzed by calculating use values (UV), relative frequency of citation (RFC) and informant consensus factor (ICF). Many use reports and species were from Leguminosae and Zingiberaceae. Roots and leaves were the most used parts, while the preferred preparation methods were decoction and burning. Oral ingestion was the most common form of administration. The most common ailment was muscle pain. Sambucus javanica and Plantago major were the most important species because they had the highest and second-highest values for both UV and RFC, respectively. This study revealed that the Karen people in Thailand use various medicinal plants to treat MSDs. These are the main resources for the further development of inexpensive treatments of MSDs that would benefit not only the Karen, but all people who suffer from MSD.